Everything Was Forever, Until It Was No More : The Last Soviet Generation - Yurchak, Alexei, 1960- (Book collections on Project MUSE., 2006)
Soviet socialism was based on paradoxes that were revealed by the peculiar experience of its collapse. To the people who lived in that system the collapse seemed both completely unexpected and completely unsurprising. At the moment of collapse it suddenly became obvious that Soviet life had always seemed simultaneously eternal and stagnating, vigorous and ailing, bleak and full of promise. Although these characteristics may appear mutually exclusive, in fact they were mutually constitutive. This book explores the paradoxes of Soviet life during the period of ""late socialism"" (1960s-1980s)